Factor influencing the implementation of Islamic work ethics in banks: a qualitative study - Melati, Putifatma Hanum; Mohd Mahudin, Nor Diana; Fauzi, Fatin; Janon, Nazariah Shar'ie (2015)
Work ethics are essential in organisations because not only they are used to guide employees to behave ethically, but they could also affect employees’ performance and efficiency. This reality necessitates a clear and effective strategy for implementation of workplace ethics policies in general and Islamic work ethics in particular. However, little systematic evaluation of such implementation processes has been made. This study aimed to explore what is known regarding the issues that facilitate the implementation of Islamic work ethics in organisations and to make recommendations for their successful implementation. A qualitative study using semi-structured interview (n = 16) with Branch Managers and Assistant Branch Managers from six Islamic banks in Kuala Lumpur and Selangor was conducted. Data saturation was reached after 12 interviews, with four additional interviews undertaken to ensure a broadly representative sample. Using thematic analysis, nine important themes describing factors influencing the implementation of Islamic work ethics were identified. These factors vary from personal and organisational to management and environmental. Improvements in these factors may have positive effects on successful implementation of ethics policies in organisations.